Effect of Thyme (Thymus vulgaris L.) leaves powder in germination and early development and protein percentage of two Durum and Aestivum wheats cultivars. - Abd Elaziz, Mohamed; Khalasi, Hussam; Barhoum, Lubna (Latakia University Journal -Biological Sciences Series, 2018)
This research was carried out in a field at" Beit Al Raheb"-Dreikeich-Tartous during the (2015-2016) season to study the effect of لاast in the province of Tartous in beit alseason in a syriaThymus vulgaris leaves powder in some physiology and protein percentage of two Durum and Aestivum wheats cultivars.The agriculture was in two locations (protected and fields under normal conditions) .Two variets of wheat were used : Cham1 and Cham4 , five concentrations of Thymus vulgaris L. leaves powder 5,10,5,20,25 (g.kg-1) were studied and control in both locations . Complete Randomized Design (RCBD) with three replications was used , for both locations to see the effect of wheat variets and concentrations and locations and the interaction between them.The Genstat12 was used statiscal analysis. The results indicates that cham1variety significantly surpassed cham4 variety in the germination percentage, protein percentage inside the seeds .In the other hand cham4 variety significantly surpassed cham1 in the length of the shoot .و , plant heigh, spike length . The concentration 5 (g.kg-1) achieved significant increase in the value of germination percentage , average germination time,length of shoot ,length of root in both location . But the concentration 25 (g.kg-1) soil achieved significant increase in protein percentage in both location . تأثير مسحوق أوراق الزعتر البريL . Thymus vulgaris في الإنبات والنمو الأولي ونسبة البروتين لصنفين من القمح القاسي والطري نُفذ البحث خلال الموسم الزراعي (2016-2015) في الساحل السوري في في حقل ضمن قرية "بيت الراهب" التابعة لمنطقة الدريكيش في محافظة طرطوس, وذلك لبيان دراسة تأثير مسحوق أوراق الزعتر البري في بعض الخصائص الفيزيولوجية ونسبة البروتين لصنفين من القمح القاسي والطري , تمت الزراعة في موقعين ( زراعة محمية وزراعة حقلية تحت الظروف الطبيعية ), تمت زراعة صنفين من القمح هما: شام1و شام4 . وتم استخدام خمسة تراكيز من مسحوق أوراق الزعتر 5, 10, 15, 20, 25(غ.كغ-1) إضافةً إلى الشاهد للمقارنة, صممت التجربة بتصميم القطاعات العشوائية الكاملة RCBD, وبثلاث مكررات لكلا الموقعين لمعرفة تأثر صنفي القمح بتراكيز الزعتر البري المضافة وموقعي التجربة وتأثير التداخل بين العوامل الثلاث (الصنف , التركيز , الموقع) في الخواص الفيزيولوجية , والنوعية . وحللت البيانات باستخدام البرنامج الإحصائي Genstat 12, وأظهرت النتائج تفوق صنف القمح القاسي (شام1 ) على صنف القمح الطري (شام4) في نسبة الإنبات , نسبة البروتين , بينما تفوق صنف القمح الطري على صنف القمح القاسي في طول المجموع الخضري والجذري . وحقق التركيز 5 (غ.كغ-1) المنخفض من مسحوق أوراق الزعتر البري زيادة معنوية في قيمة نسبة الإنبات, متوسط زمن الإنبات, طول المجموع الخضري , طول المجموع الجذري في كلا الموقعين. بالمقابل سبب التركيز 25 (غ.كغ-1) تربة من مسحوق أوراق الزعتر البري زيادة معنوية في نسبة البروتين .